Entrepreneurship, College and Credit: The Golden Triangle - Samaniego, Roberto M (Institutional Knowledge at Singapore Management University, 2016)
We develop a model to evaluate the impact of college education finance on welfare, inequality and aggregate outcomes. Our model captures the stylized fact that entrepreneurs with college are more common and more profitable. Our calibration to US data suggests this is mainly because higher labor earnings allow college educated agents to ameliorate credit constraints when they become entrepreneurs. The welfare benefits of subsidizing education are greater than those of eliminating financing constraints on education because subsidies ameliorate the impact of financing constraints on would-be entrepreneurs.